Temporal assessment of radiation exposure to uterus and ovaries in simulated scopy during hip fracture repair: A phantom study - Gunay, Osman; Canturk, Ismail; Kekec, Eylem; Aksoy, S. Hilmi (ELSEVIER, 2024)
This study systematically explores the temporal variations in radiation dose incurred by reproductive organs during simulated scopy procedures. Focusing on a simulated scenario of repairing a fictitious right hip fracture, the investigation utilizes the Alderson Rando phantom and Thermoluminescent Dosimeters (TLDs) to meticulously examine the dynamics of radiation exposure. The study employs TLD-100 dosimeters placed in specific regions of the phantom, mimicking the right and left ovaries and uteri. The scopy simulation is conducted to replicate a procedure, with the X-ray tube's exposure duration ranging from 0.5 to 8 min. The dosimeters are then analyzed to determine the radiation doses incurred during different time intervals. In conclusion, this study provides valuable insights into the dynamic nature of radiation exposure to reproductive organs during simulated scopy procedures. The presented data contribute to our understanding of how exposure duration and anatomical positioning influence radiation doses. Additionally, the strong positive correlation between the duration of X-ray tube exposure and incurred radiation dose underscores the reliability of the scopy system in maintaining consistent radiation levels over time. The calculated average dose rates for the right ovary, left ovary, right uterus, and left uterus are 6.768 +/- 0.461, 2.656 +/- 0.289, 3.724 +/- 0.283, and 3.202 +/- 0.223 mSv/min, respectively. This study lays the groundwork for future research on optimizing radiation exposure in scopy procedures to minimize potential risks while ensuring effective medical imaging.
Keywords: Scopy; Radiation exposure; Uterus; Ovaries; Phantom study; Temporal analysis; Dose-rate; SHIELDING PROPERTIES; ATTENUATION; PREGNANCY; CONCRETE; BARITE; Science & Technology - Other Topics; Radiology, Nuclear Medicine & Medical Imaging